(untitled) (Fiep Bulletin - online, 2011)
Sport as a content of Physical Education, in the cultural context of body movement, was historically the result of changing public policies in education that were not on the sidelines of society. From this, the sport is presented as hegemonic content during the process of teaching and learning in physical education classes at school, as well as other cultural forms are being esportivizadas by holding competitions and standardizing the rules. In this sense, this paper aims at discussing the main manifestation of the sport from the school context, in order to uncover the practice observed in Brazilian schools. This was a qualitative research of bibliographical. As a result of this study, we believe that the sport worked in physical education will only have an effect, especially, social, considering the learner as an active agent in the teaching process, allowing the understanding of the entire movement and not a repetition of simple gestures mechanics and technicians.